To Carlos on his sixtieth birthday: Greetings from your friends in Iowa - Philip C. Kutzko (Mathematical Biosciences and Engineering)
It is hard, now, to imagine a time when our math department's graduate program had no minority students. The diversity of our program has become so familiar to us that when, this spring and summer, seven of our minority students earned their doctoral degree it was hardly commented on. Indeed it was only when we began to miss these students -- students who were like family to us -- that the reality of this singular achievement manifested itself to us. Yet there was indeed a time when there were no minority graduate students in mathematics at the University of Iowa. In fact, only two minority students earned their doctoral degrees from our department from1974, when I joined the department, to 1998. And it is no exaggeration at all to state that, without the trust and support of Carlos Castillo-Chavez, it is unlikely that the transformation of our graduate program that took place over the past fifteen years would have occurred.For more information please click the “Full Text” above.